Integrasi Pendekatan Sosio-Psikolinguistik Dalam Pembelajaran Bahasa Arab Di Era Modern - Leoni Wilyam; Anisa Eka Putri Aulia; Aura Zammiya; Afifa Mawada; Sahkholid Nasution (Yayasan Salam Cerdas Al-Fattah, 2025)
This study examines the integration of the socio-psycholinguistic approach in learning Arabic in the modern era, as well as its implications for language skills, vocabulary retention, and learner motivation. The method used is descriptive qualitative. Data were collected through in-depth interviews, classroom observations, and curriculum documentation. Data analysis followed three main stages: data reduction, data presentation, and conclusion drawing. The results showed that the application of the socio-psycholinguistic approach that combines the cognitive aspects of psycholinguistics with the socio-cultural dimensions of sociolinguistics has a positive impact in the form of improved communication skills in Arabic, long-term vocabulary retention, and higher learning motivation. However, implementation in the field is still constrained by gaps in teacher competence, a curriculum that does not fully support contextual learning, and limited digital infrastructure in less developed areas.